Energy Transition Indicators in African Countries: Managing the Possible Decline of Fossil Fuels and Tackling Energy Access Challenges - Nalule , Victoria; Acheampong, Theophilus (Journal of Sustainable Development Law and Policy, 2025)
The global move to tackle climate change as envisaged in the 2015 Paris Agreement has necessitated debates and action geared towards transitioning to a low carbon economy. Although there is no agreed international definition of energy transition, the focus has been put to a shift from fossil fuels to renewables. This paper is intended to contribute to the global debate on energy transition with a focus on the initiatives taking place in a few selected countries. The argument in this paper is to the effect that many developing countries still need fossil fuels to tackle energy access challenges and ensure economic growth. Nevertheless, this does not in any way mean that these countries are climate change deniers. In this respect, the question to be addressed in this article is how can we measure energy transition efforts in developing countries? In responding to this question, the article attempts to develop and analyse some key energy transition indicators.